Splenic Metastasis of Squamous Cell Carcinoma of the Uterine Cervix: A Case Report and Review of the Literature - Shigeki Taga; Mari Sawada; Aya Nagai; Dan Yamamoto; Ryoji Hayase (Case Reports in Obstetrics and Gynecology)
Metastasis from various neoplasms to the spleen is very rare and most of the cases are found at autopsy. We report a patient presenting with uterine cervical cancer with splenic metastases. A 49-year-old woman presenting with genital bleeding was referred to our hospital and diagnosed with stage IIB cervical cancer. She underwent concomitant chemoradiotherapy (CCRT) consisting of 50 Gy whole pelvis irradiation, high-dose-rate intracavitary brachytherapy 24 Gy/4 fractions and six weeks of paclitaxel and carboplatin administration. Ten months after the initial therapy, CT revealed recurrence at spleen. Although she received 5 courses of nedaplatin, enlargement of the tumor was noticed. She underwent a splenectomy and the result of histology was compatible with metastasis of cervical cancer.